EFEKTIFITAS PEMAKAIAN DAYA PADA PROTOTIPE ESKALATOR DENGAN PLC DAN NON - PLC - A.R. Fadli Janaldi; Sukaya Sukaya; Almasri Almasri (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The research begining from the real in the Department Store and Mall so many to see Escalator that is a tool can be bring object from under floor to upper floor or opposite. Escalator always on from begining the mall open  until with  the mall close everydays certainly need too big  power and money must be buying every month for that power used. Programmable Logic Controller ( PLC ) is a digital electronics system / special type control have  as a base microprocessor using the memory can be program  for saving the instruction – instruction  and order the tool  will be control. Seen the symptom  then  can be formula the problem in this research that is how to abate power used escalator in the mall city of Padang involve the use of tool controlling that is PLC pass through of analysis of escalator prototype. Type this research is a experiment  in the research  researcher try to observation and manipulation the research object with a control. Researcher do at act of planning program, escalator with PLC control  and measurement used power of this escalator  prototype  and comparable with escalator prototype  without  PLC control in this prototipe. The result seen that escalator prototype non – PLC needed the power in 3 hour ( 116,84 Ampere ) too high if compare with escalator prototype with PLC is (62,65 Ampere ). Like that with torque when no load 0,5 Nm  for prototype non – PLC but 0 Nm for prototype with PLC and speed 413 Rpm  for escalator prototype non – PLC  than 400 Rpm  for escalator prototype with PLC when the load 2,5 Kg.Keywords :Escalator, Programable Logic Controller (PLC), LimitSwitch